Kinetics and Mechanism of Oxidation of Ethyl Diethylene Glycol by Ce(IV) Catalyzed by Ir(III) in Aqueous Sulphuric Acid Media - Singh, Kamini; Kumar Singh, Ashish; Jaiswal, Jaya; Singh, R.A. (Asian Journal of Chemistry, 2010)
The kinetics of iridium(III) catalyzed oxidation of ethyl diethylene glycol by ceric sulphate has been investigated in sulphuric acid media. The result indicates zero order kinetics with respect to cerium(IV) ion and first order kinetics with respect to ethyl diethylene glycol and iridium(III) chloride. The dielectric constant of the medium shows positive effect on the reaction rate. There is insignificant effect of ionic strength of potassium sulphate on the reaction rate indicating interaction in the rate-determining step being an ion-dipole type and not an ion type. Elevation of temperature increases the rate of reaction. Various activation parameters have been calculated and recorded. A suitable mechanism in conformity with the above observation has been proposed.